Kontribusi Komunikasi Orang Tua Terhadap Karakter Religi Remaja di Desa Pematang Gajah Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Fitri Yuniarti; Rabiatul Adawiyah (Lembaga Pengembangan Kinerja Dosen, 2026)
The family is the first environment that plays an important role in shaping adolescents’ religious character. Communication between parents and children serves as the primary means of instilling religious values, moral principles, and social behavior. Adolescents who maintain good communication with their parents tend to demonstrate more positive religious attitudes. This study aims to examine the contribution of parental communication to the relisgious character of adolescents in Pematang Gajah Village, Jambi Luar Kota District, Muaro Jambi Regency. This study employed a quantitative approach with a correlational research design. The research sample consisted of 98 adolescents selected from a population of 130 individuals using the Slovin formula. Data were collected through Likert-scale questionnaires measuring aspects of parental communication (openness, empathy, intensity, and emotional support) and adolescents’ religious character (activeness in worship, honesty, politeness, and religious participation). Data analysis was conducted using normality tests, linearity tests, and simple linear regression. The results indicate that both parental communication and adolescents’ religious character fall within the moderate category. There is a significant contribution and a linear relationship between parental communication and adolescents’ religious character. These findings emphasize the importance of family communication in fostering adolescents’ religiosity